1954
DOI: 10.2355/tetsutohagane1915.40.8_779
|View full text |Cite
|
Sign up to set email alerts
|

Study on Boron Steel (I)

Abstract: Synopsis:The purpose of boron treatment is to improve the hardenability of steel by addition of small emounts of boron less than 0.005%, and to save the alloying elements, nickel, chromium, and molybdenum. In Japan, there have been some basic investigations about the boron steel, but little experience in producing it.In order to promote the use of boron steel successfully, the authors believed, it was necessary to study the influence of boron addition on the steels specified in Japanese Industrial Standards.Ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nagata et al reported the transfection of Saccharomyces cerevisiae protoplasts with liposome-encapsulated plasmid DNA, 8) and the delivery of 6-carboxyfluorescein into Sacch. cerevisiae protoplasts mediated by liposomes which were made of phospholipids extracted from the same yeasts was reported by Yamanaka et al 9 ) But the details of liposome protoplast interactions were left unknown. Therefore it seems valuable to find hether or not liposomes can introduce membrane-impermeable substances into yeast protoplasts, and if possible, to discover the factors which affect the efficiency of delivery of liposomal content into yeast protoplasts drastically.…”
mentioning
confidence: 91%
“…Nagata et al reported the transfection of Saccharomyces cerevisiae protoplasts with liposome-encapsulated plasmid DNA, 8) and the delivery of 6-carboxyfluorescein into Sacch. cerevisiae protoplasts mediated by liposomes which were made of phospholipids extracted from the same yeasts was reported by Yamanaka et al 9 ) But the details of liposome protoplast interactions were left unknown. Therefore it seems valuable to find hether or not liposomes can introduce membrane-impermeable substances into yeast protoplasts, and if possible, to discover the factors which affect the efficiency of delivery of liposomal content into yeast protoplasts drastically.…”
mentioning
confidence: 91%